2000
DOI: 10.1063/1.480883
|View full text |Cite
|
Sign up to set email alerts
|

Pulse radiolysis studies on charge carriers in conjugated polymers

Abstract: The charged states of the conjugated polymers poly(2-methoxy,5-(2′-ethylhexyloxy)-p- phenylenevinylene) (MEH-PPV) and poly(2,5-pyridinediyl) (PPY) have been studied by pulse radiolysis. Following pulse radiolysis of argon-saturated solutions of MEH-PPV in chloroform, a new absorption is seen to grow in over a few hundred microseconds. This has a principal absorption at 1.43 eV and a weaker, low energy band (⩽0.80 eV), and is assigned to the positive one-electron charge state (positive polaron) of MEH-PPV. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…The one-electron reduced species from MEH-PPV has also been prepared by pulse radiolysis in benzonitrile solution [26]. The spectrum is similar, but appears to show a small solvent shift.…”
Section: Negative Charge Carriersmentioning
confidence: 88%
See 2 more Smart Citations
“…The one-electron reduced species from MEH-PPV has also been prepared by pulse radiolysis in benzonitrile solution [26]. The spectrum is similar, but appears to show a small solvent shift.…”
Section: Negative Charge Carriersmentioning
confidence: 88%
“…We have shown that this can be used to unambiguously prepare the positive charge carriers of conjugated polymers [23,26]. We will take MEH-PPV as a typical case.…”
Section: Positive Charge Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported on the use of pulse radiolysis to measure the triplet energy in poly[2-methoxy,5-(2 0 -(ethylhexoxy)-p-phenylenevinylene] (MEHPPV) [7]. We have also demonstrated that charged states, again generated by this method, have very different lifetimes and spectral signatures from the triplet states [11]. We now report on triplet state measurements on a range of the most widely used luminescent and conductive polymers in current display technologies; see Fig.…”
mentioning
confidence: 99%
“…This will favour Fo Èrster-type [14] triplet energy transfer from excited states of conjugated polymers. The triplet energies of a series of conjugated polymers have recently been determined [15,16]. Matching the energies of these with the lowest triplet states of polypyridylruthenium(II) complexes may provide a method for highly ef®cient , where tpy and py are 2,2 0 ,2 00 -terpyridine and pyridine, and L±L represents the bidentate ligands bipyridyl (bpy), 4,4 0 -dimethylbipyridyl (Me 2 bpy), 4-nitrobipyridyl (O 2 Nbpy), oxalate (ox) and acetylacetonate (acac) [17].…”
Section: Introductionmentioning
confidence: 99%